Habitat decline of the largest known Indo-Pacific humpback dolphin (Sousa chinensis) population in poorly protected areas associated with the hypoxic zone - Guo, Lang; Luo, Dingyu; Yu, Ri-Qing; Zeng, Chen; Huang, Nuoyan; Wang, Hongri; Wu, Yuping (Frontiers in Marine Science, 2022)
Reserve planning based on the investigation of the core habitat distribution of wild cetaceans is a powerful conservation strategy for protecting target species. However, studies on core habitats and their variations at the large-scale distribution of cetaceans are limited. In this study, we conducted a seven years (2015-2021) boat-based field observation surveys with highly applicable and generalized methods to analyze the habitat changes and how these changes influenced the largest known Indo-Pacific humpback dolphin (Sousa chinensis) population in the Pearl River Estuary (PRE), China. Our findings revealed that there is 3204 km2 of dolphin habitat in the PRE, and dolphin distribution preferences are related to nutrients and biological resources. The decreasing trend of dolphin sighting rates in most areas (73.2%) indicated that the dolphin habitat had declined, and the annual habitat decline rate (2.83%; 95% confidence interval: 0.58%-5.08%) was consistent with the population decline rate. The annual habitat decline rate in the hypoxic zone revealed that low dolphin sighting rates from March to October in the hypoxic zone was 0.43% faster than that in the non-hypoxic zone, indicating long-term sustained effects of summer hypoxia on the dolphin population. Existing reserves have partially prevented habitat decline. However, more than 82.3% of the habitat has not been effectively protected and encounters the threats of pollution and hypoxic stress. This study offers new scientific evidence for developing effective monitoring strategies for humpback dolphin populations in the PRE, and also help establish spatial planning and management measures for reserve habitats.